2018
DOI: 10.1093/nar/gky1239
|View full text |Cite
|
Sign up to set email alerts
|

Diverse lipid conjugates for functional extra-hepatic siRNA deliveryin vivo

Abstract: Small interfering RNA (siRNA)-based therapies are proving to be efficient for treating liver-associated disorders. However, extra-hepatic delivery remains challenging, limiting therapeutic siRNA utility. We synthesized a panel of fifteen lipid-conjugated siRNAs and systematically evaluated the impact of conjugate on siRNA tissue distribution and efficacy. Generally, conjugate hydrophobicity defines the degree of clearance and the liver-to-kidney distribution profile. In addition to primary clearance tissues, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
159
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 52 publications
2
159
0
1
Order By: Relevance
“…The biodistribution of various lipophilic siRNA conjugates has been extensively studied in a recent paper (Biscans et al, 2018). It was shown that cholesterol conjugates were more effectively retained in the body (62%) compared with other lipophilic conjugates (27–62%).…”
Section: Bioconjugatesmentioning
confidence: 99%
See 3 more Smart Citations
“…The biodistribution of various lipophilic siRNA conjugates has been extensively studied in a recent paper (Biscans et al, 2018). It was shown that cholesterol conjugates were more effectively retained in the body (62%) compared with other lipophilic conjugates (27–62%).…”
Section: Bioconjugatesmentioning
confidence: 99%
“…Following subcutaneous injection, the cholesterol conjugates accumulated in almost all organs: liver, kidney, adrenal glands, spleen, pancreas, heart, muscle, fat, thymus, lung, injection site, ovaries, and testes. At the same time, cholesterol conjugates accumulated most effectively in the liver, adrenal glands, spleen, and in the skin at the site of administration (Biscans et al, 2018). Cholesterol derivatives accumulated in other organs with the same or lesser efficiency than other lipophilic conjugates; e.g., it was shown that a conjugate of siRNA and saturated fatty acid (docosanoic, C21) accumulated more efficiently than a cholesterol conjugate and inhibited expression of the target gene ( Htt or Ppib ) in muscles (20 and 30% inhibition of Htt and Ppib , respectively) and fat (50% and 30% inhibition of Htt and Ppib , respectively) after subcutaneous injection (20 mg/kg) (Biscans et al, 2018).…”
Section: Bioconjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficient and stable insertion into live cell membranes allows amphiphilic DNA conjugates to cross the cell membrane . Importantly, these DNA amphiphiles can be modified with additional functional groups that enable specific targeting and biocompatibility in vivo, providing them with a tremendous potential for biomedicine …”
Section: Introductionmentioning
confidence: 99%